Acaso e indeterminação no processo de composição: um diálogo com a obra de John Cage - Nathalia Angela Fragoso Rossi (2015)
This dissertation is a reflection on the compositional process of two pieces from John Cages aleatoric and indeterminate period, Music of Changes (1951) and Concert for Piano and Orchestra (1957), using as main source of reference the book The Music of John Cage (Pritchett, 1993). These were chosen mainly for the compositional methods applied as well as changes in the role the composer plays. In parallel with the study of the pieces, three compositions People expect listening to be more than listening for percussion and electronics, Pulsações for prepared piano and light and Não tenho nada a dizer e estou dizendo for voice and electronic were developed and analyzed aiming to demonstrate the relationship established with the compositional processes of Cage.